Making a feature length documentary film linked to the programme for improving mental health care (PRIME) : process and ethical challenges - Makan, Amit J (Centre for Film and Media Studies, 2016)
Globally mental health is widely regarded by scholars as a neglected public health issue. Documentary film is recognised as an appropriate medium for addressing social and political issues, and mental health is both of these. Country comparative documentary films on mental health, set in low and middle-income countries, appear to be lacking. Prorgramme for Improving Mental health carE (PRIME) works in five low and middle income countries, two of which were selected for the film (Nepal and South Africa). This was motivated by across continent comparisons, financial and logistical viability within a one year timeframe, global interest and appeal and the support of PRIME colleagues and local country partners. Based on qualitative research including a literature review and 40 indepth interviews with stakeholders, this essay reports on, and critically assesses the ethical and production processes involved in making the documentary film. The essay includes several elements. Firstly, it considers the power relationship between the filmmaker and the subject. Whilst Nichols, Aufderheide and colleagues present useful ethical considerations for making a documentary film, both from the subject and audience perspectives, more care is required when making a film with persons living with mental illness. This is particularly because the subject may not have the mental capacity to consent, and if they do, participating in the media production process could potentially exacerbate their condition. Having weighed these risks up with the benefits of representing persons living with mental illness, and giving them a voice, the decision was made to give persons living with mental illness the opportunity to represent themselves. Secondly, and having made the decision to allow for representation, the various documentary modes (expository, performative, poetic, observational, reflexive, participatory) conceived by Nichols were explored, in an attempt to identify a conceptual framework for the film. The performative mode was most appropriate for telling deeply personal stories, and providing patients with an opportunity to be represented. However, this mode was ideally complemented with elements of the expository (verbal commentary of experts), poetic (use of rhythm, emotion and music), observational (footage of patients in their daily routines, and of their environment for cutaways) and participatory (through direct engagement between filmmaker and subject) modes. 2 Having identified a conceptual framework, the third element involved the institutional research ethics processes. These processes contributed to a more ethically sensitive film production. This included a check for mental health service users to ensure that they do have the capacity to consent. The process of developing a research protocol highlighted the synergistic benefits of integrating a qualitative research method in the form of in-depth interviews into the film production process (and vice versa), whilst remaining cognisant of not compromising research findings for more visually appealing footage. Following a research process for the production also contributed to a more robust discussion guide after translating communication objectives into research objectives. Finally, the process of implementing the film's production, and post-production, was assessed. A host of steps were identified, which included securing the funding for the filmmaking, establishing stakeholders support, briefing the crew on the vision and purpose of the documentary and having access to equipment and translators. During the post production process, a systematic approach to editing using a script outline was helpful in identifying main themes, and to ensure the narrative flow. Despite its typical use in fictional filmmaking, the three-act structure was fitting as a framework for the narrative. Timecoding during translation and transcription was found to be particularly expedient for inserting English sub-titles. The country comparative approach revealed similaries and differences, and developing and implementing stakeholder specific distribution strategies (including conferences, symposia, film festivals and broadcasters) was identified as critical to the public dissemination and reach of the film. Documentary film, and the performative mode complemented by other modes, has shown to be an advantageous means of representing persons living with mental illness, and their families. However, the paper calls for more evaluation research regarding the impact of the film on the main patient characters, amongst other stakeholders such as health workers and policy makers. The paper also proposes the integration of media production into a research process for researchers interested in using this medium to visually communicate their research findings, emphasising the value of systematically using the research findings to develop a narrative script in the context of a typical three act structure. A distribution strategy was also identified as necessary to maximise the research and stakeholder impact of the film.